Estudo quimiossistemático de espécies de Hortia (Rutaceae) e busca de fungicidas à Guignardia citricarpa - Freitas, Samya Danielle Lima de (2010)
The classification of the Hortia genus, belonging to the Rutaceae, is ambiguous. Hortia, which has been placed in Cusparieae by De Candolle in 1824, in the most recent morphological classification of Engler in 1931 it belongs to Toddalieae. More recently, Silva and colleagues classified again Hortia in Cusparieae. However, the phytochemical study of the species from Hortia genus still not allow classify correctly it inside the family. Thus, the phytochemical study of Hortia described in this paper aims to contribute with the chemosystematics of the Rutaceae and with the best classification of the genus inside the family. The study of the species H. oreadica, H. brasiliana and H. superba led to the isolation and identification of 11 substances, the alkaloids N-methyl-4- methoxy-quinolin-2-one (01), integriquinolone (02), new in the genus Hortia, rutaecarpine (03), the coumarins scoparone (04) xanthotoxin (05), which were first described in the species H. superba, isopimpinellin (06), new in the genus Hortia, 5- chloro-8-methoxy-furanocoumarin (07), new in the literature, prangol (08) and heraclenol (09), and the flavonoids isosakuranetin (10) and neoponcirin (11), the latter being new in the genus Hortia. The presence of metabolites such as alkaloids, coumarins and flavonoids confirm that Hortia belongs to the Rutaceae family, even so are not clear its accurate positioning. Some of the isolated compounds were tested against the inhibition of Guignardia citricarpa following two methods of inhibition assays. One based on inhibition of G. citricarpa in vitro against growth mycelial, by the method of incorporation into the culture medium. The other based on the inhibition test to G. citricarpa in vitro on spore germination and appressorium formation by the method of germination of spores on plates of polystyrene. The first methodology only evaluated the inhibition of the formation of mycelia and it is not directly involved in the infection process of plants, already the second one evaluated the inhibition of reproductive structures of microorganisms (spores), responsible for the infection process. The average growth mycelial for all substances tested revealed the alkaloid N-methyl-4-methoxy-2-quinolin-2-one (100 μg.mL-1) as the most effective among all the substances tested. As the inhibition front of spore germination and appressorium formation, the results were quite satisfactory, the coumarin scoparone (100 μg.mL-1) showed 96% of inhibition spore germination and 99% for the formation of appressorium, the alkaloid N-methyl-4-methoxy-2-quinolin-2-one (100 μg.mL-1) with 83% and 91%, and the flavonoid isosakuranetin (100 μg.mL-1) with 71,4% and 80%, respectively. Therefore, from this study it was found that some natural products with antifungal activity revealed important sources in the discovery of new products free of toxicity and effective as a fungicide.